The Impact of School Improvement Grants on Student Outcomes: Findings From a National Evaluation Using a Regression Discontinuity Design. Issue 2 (3rd April 2019) - Dragoset, Lisa; Thomas, Jaime; Herrmann, Mariesa; Deke, John; James-Burdumy, Susanne; Lee Luca, Dara
Abstract: As part of the American Recovery and Reinvestment Act of 2009, the School Improvement Grants (SIG) program received more than 3 billion with the goal of substantially improving student achievement. The SIG program's funding was to help states turn around the nation's persistently lowest-achieving schools using one of four school intervention models—transformation, turnaround, restart, or closure. We used a regression discontinuity design and a large sample of schools from more than 20 states to evaluate the impact of implementing a SIG-funded intervention model on use of SIG-promoted practices and student outcomes. Our regression discontinuity design exploited cutoff values on the continuous variables used to define the SIG eligibility tiers to compare outcomes in schools that just met the eligibility cutoff for receiving SIG funding to outcomes in schools that just missed it. We found that SIG had no impact on any of the outcomes we examined, including math and reading test scores, high school graduation rates, and college enrollment rates. Using a correlational analysis, we found the turnaround model was associated with larger student achievement gains in math than the transformation model for grades 6 through 12.